Free speech from core values to current debates - Niehoff, Leonard M. 1957-; Sullivan, E. Thomas 1948- (Cambridge University Press, 2022)
Why do we protect free speech? What values does it serve? How has the Supreme Court interpreted the First Amendment? What has the Court gotten right and wrong? Why are current debates over free expression often so divisive? How can we do better? In this succinct but comprehensive and scholarly book, authors Len Niehoff and Thomas Sullivan tackle these pressing questions. Free Speech: From Core Values to Current Debates traces the development and evolution of the free speech doctrine in the Supreme Court and explores how the Court - with varying levels of success - has applied that doctrinal framework to "hard cases" and current controversies, such as those involving hate speech, speech on the internet, speech on campus, and campaign finance regulation. This is the perfect volume for anyone - student, general reader, or scholar - looking for an accessible overview of this critical topic
Title from publisher's bibliographic system (viewed on 07 Apr 2022)
Instrumental value arguments for free speech -- Instinct value arguments for free speech -- Free expression and due process values -- The everyday First Amendment -- The First Amendment prior to 1919 -- The First Amendment from 1919 to 1963 -- The First Amendment from 1964-present : hard cases -- Content and Viewpoint restrictions are disfavored -- Vagueness and overbreadth are special concerns -- Exceptions must be limited and narrowly crafted -- Hate speech -- Campaign finance regulation -- Speech in public schools -- Academic freedom -- Speech on the internet -- Our hazardous freedom
Keywords: Freedom of speech / United States; Meinungsfreiheit; Redefreiheit; USA